Long-Term Management of Venous Thromboembolism: Lessons from EINSTEIN CHOICE and Other Extension Trials - Weitz, Jeffrey I.; Chan, Noel C. (Thrombosis and Haemostasis, 2019)
Many patients with venous thromboembolism (VTE) are at risk of recurrence if anticoagulant therapy is stopped. Whereas 3 months of anticoagulation treatment is sufficient for patients with VTE provoked by major surgery or trauma, in many cases a longer course is needed. Extended therapy with vitamin K antagonists (VKAs) requires frequent coagulation monitoring and dose adjustments to ensure that the international normalized ratio (INR) remains within the therapeutic range; furthermore, there is a risk of major bleeding even if a therapeutic INR is maintained. Therefore, more convenient and safer anticoagulants are needed.The non-VKA oral anticoagulants (NOACs)—apixaban, dabigatran, edoxaban and rivaroxaban—simplify extended therapy because they can be given in fixed doses without routine coagulation monitoring. Randomized clinical trials have demonstrated the efficacy and safety of NOACs for extended VTE treatment, but bleeding remains a concern. Patients and physicians may, therefore, be reluctant to continue anticoagulation beyond 3 to 6 months except in patients at high risk of recurrence. Acetylsalicylic acid (ASA) is often prescribed instead of an anticoagulant because of its perceived lower risk of bleeding; however, the recent EINSTEIN CHOICE trial demonstrated that once-daily rivaroxaban at a dose of either 20 or 10 mg reduced the risk of recurrent VTE by 70% compared with ASA without significantly increasing the risk of bleeding. In this review, we discuss the EINSTEIN CHOICE trial in the context of previous trials for extended VTE treatment and examine some of the lessons that can be applied to clinical practice.
Keywords: venous thromboembolism; anticoagulation; extended therapy; rivaroxaban; acetylsalicylic acid